2011
DOI: 10.1158/1535-7163.mct-11-0421
|View full text |Cite
|
Sign up to set email alerts
|

Digitoxin-Induced Cytotoxicity in Cancer Cells Is Mediated through Distinct Kinase and Interferon Signaling Networks

Abstract: Cardiac glycosides (e.g., digoxin, digitoxin) constitute a diverse family of plant-derived sodium pump inhibitors that have been in clinical use for the treatment of heart-related diseases (congestive heart failure, atrial arrhythmia) for many years. Recently though, accumulating in vitro and in vivo evidence highlight potential anticancer properties of these compounds. Despite the fact that members of this family have advanced to clinical trial testing in cancer therapeutics, their cytotoxic mechanism is not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 36 publications
2
55
1
5
Order By: Relevance
“…The list of upregulated proteins identified by LC-MS/MS was analyzed by pathway analysis using the network-building tool, Ingenuity Pathways Analysis (IPA; Ingenuity Systems, http://www.ingenuity.com), as previously described [51]. …”
Section: Methodsmentioning
confidence: 99%
“…The list of upregulated proteins identified by LC-MS/MS was analyzed by pathway analysis using the network-building tool, Ingenuity Pathways Analysis (IPA; Ingenuity Systems, http://www.ingenuity.com), as previously described [51]. …”
Section: Methodsmentioning
confidence: 99%
“…In particular, in vitro studies showed that exposure of non-small lung cells, renal, pancreatic and breast cells to micromolar concentrations of digitoxin (0.5–5 μM) inhibits Na + /K + -ATPase pump activity (López-Lázaro, 2007; Newman et al, 2008), induces calcium-dependent activation of caspases and other hydrolytic enzymes (Einbond et al, 2008; Elbaz et al, 2012a), causes generation of reactive oxygen species (Prassas et al, 2011), activates the cell-cycle inhibitor p21Cip1 (Prassas et al, 2011), directs the inhibition of topoisomerase activity and hypoxia-inducible factor1a synthesis (Sun et al, 2013), and ultimately reduces viability and cell proliferation (Elbaz et al, 2012a; Menger et al, 2013). Complementary, cellular exposure to nanomolar concentrations of digitoxin (10–100 nM) leads to inhibition of (HIF-1) and topoisomerase II synthesis (Prassas et al, 2011), activation of phospholipase C (Elbaz et al, 2012a; Ho et al, 1987), phosphatidylinositol-3-kinase (PI3K) (Ho et al, 1987), tyrosine kinase (Src) (Elbaz et al, 2012a; Jagielska et al, 2009), mitogen-activated protein kinase (MAPK) (Prassas et al, 2011), affects cell cycle and anoikis (Pongrakhananon et al, 2014) inducing alternations in membrane fluidity (Larre et al, 2010; Xie and Cai, 2003), ultimately leading to cell apoptosis (Lopez-Lazaro et al, 2005). However, the nature of these in vitro studies only allowed for discrete time points monitoring and limited analysis of the cellular functions upon exposure, all after invasive or destructive preparation of the samples, as well as labor intensive and time consuming analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the transport function of the Na + / K + -ATPase has been investigated extensively in the past, during the last decade multiple lines of evidence have suggested a number of other functions for the sodium pump, revealing NaK as (i) a multifunctional protein with key roles in the formation and maintenance of adhesion complexes, induction of epithelial cell tight junctions and polarity, cell adhesion, motility, and actin dynamics [10][11][12][13][14][15][16][17][18], (ii) a signalling protein [19][20][21][22][23][24][25][26], and (iii) a valuable novel target in anti-cancer therapy because its aberrant expression and activity are implicated in the development and progression of a growing number of cancers [27][28][29][30][31][32][33][34][35][36][37][38]. In addition to the growing number of scientific publications, a number of inventions (recently reviewed in [39]) have also emphasised the potential usefulness of considering NaK expression for future anti-cancer therapy by using it as a diagnostic and prognostic tool, as a biomarker of a therapeutic response in cancer chemotherapy with CS, and as a valuable new target.…”
Section: Resistance Of Cancer Cellsmentioning
confidence: 99%
“…Within the past 15 years, there has been a marked increase in the number of reports of CS-induced anticancer effects (recently reviewed in [26,27,37,39,45,47,48]). While in vitro anti-cancer properties of CS have been widely studied, few publications have demonstrated their in vivo activity in animal models or in clinical studies.…”
Section: Mini Reviewsmentioning
confidence: 99%